Illness as a valid reason for restoring the term of inheritance acceptance - E. A. Khodyreva; P. M. Khodyrev (Правоприменение, 2024)
The subject. Compliance with the term for the implementation of the inheritance rights for persons wishing to become successors of a deceased citizen is an important condition for acquiring rights to hereditary property. Nevertheless, frequently, owing to various reasons, citizens from among the heirs cannot comply with the procedure established by law, which, in most cases, engenders the need referring to the court with a inquire about extension of the deadline to recognize the right to inherited property. The court will be able to satisfy the stated requirements if there is a valid reason, which prevented the heir from exercising his right.The purpose of the article.The authorsdare to determine whether a disease, including a new coronavirus infection COVID-19, can be considered as a respectful reason for a recovery period for acceptance of the inheritance. The established objective has determined the need to solve the following tasks: (1) to analyze the legal reasoning of the disputed issue in the doctrine; (2) to study jurisprudence on the subject of the study; (3) to assess how fully the rules of Article 1155 of the Civil Code of the Russian Federation are applicable in relation to the citizens from whom it is potentially impossible to get out of a diseased state; (4) to offer our own perspective on the issue.Research methods are systematic approach and formal legal analysis of doctrinal sources and the existing Russian legislation and law application practice.The main results of a study. It is shown that not every painful condition can be regarded as a valid reason for restoring the term of inheritance acceptance under Article 1155 of the Civil Code of the Russian Federation. The existing science means do not allow us to formulate a final conclusion on the issue under study. Therefore, taking into account the evaluative nature of the rule applied, only the law enforcement body is able to make a decision, fully analyzing the relevant circumstances.Conclusions.When considering cases on the restoration of the term of acceptance of inheritance due to illness, the courts need to take into account a combination of factors: the nature of the disease, its duration, treatment conditions, prognosis of the disease, the degree of social adaptation of the heir. The rules of Article 1155 of the Civil Code of the Russian Federation regarding the establishment of a six-month period for applying to the court need to be revised. Their use is unjustified, and compliance is impossible in the event that a person's exit from a painful state is not expected, while due to the course of the disease, the heir is unable to declare his rights.